Relationship between Maternal Factors and Low Birth Weight (LBW) at PKU Muhammadiyah Gamping Hospital - Della Winanti; Elika Puspitasari (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: In 2020, the number of Infant Mortality Rates reached 2.4 million people due to LBW (34.5%). LBW contributes 60 to 80% of all infant deaths. LBW is babies born weighing less than 2500 grams. LBW has problems if the baby does not die at the time of birth, it will have a risk of growing and developing slowly, stunting, affected by non-communicable diseases, anemia, and impaired heart function. Purpose: To determine the relationship between maternal factors and the incidence of LBW at PKU Muhammadiyah Gamping Hospital. Methods: This research used a quantitative analytic survey with a case-control approach. This study used medical record data and maternal cohorts. The population in this study was 604 newborn babies at PKU Muhammadiyah Gamping Hospital with a total sample of 142 respondents. The sampling technique used is purposive sampling. This study employed the master table as a data collection method. The data analysis used is the chi-square test. Results: Based on the results of chi-square analysis, maternal parity (p-value = 0.228) with OR = 1.518, gestational age (0.000) OR = 15.200, multiple pregnancies (0.009) and OR = 10.161, and preeclampsia (0.164) and OR = 0.571. Conclusion: There is a significant relationship between gestational age and multiple pregnancies with the incidence of LBW. Meanwhile, parity and preeclampsia do not have a significant relationship with the incidence of LBW. It is recommended for every pregnant woman to carry out routine check-ups during pregnancy to prevent the occurrence of LBW